TRANSLATION STRATEGIES IN SCIENCE FICTION: LINGUISTIC AND CULTURAL ADAPTATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The translation of science fiction literature presents significant linguistic and cultural challenges due to its reliance on imaginative language, neologisms, and speculative concepts. This paper explores the major translation strategies used in rendering dystopian science fiction texts from English into other languages. Particular attention is given to the adaptation of culturally specific elements, preservation of stylistic features, and the translation of newly coined terms. The study demonstrates that successful translation in this genre requires a balance between fidelity to the source text and creative adaptation to the target culture. The findings emphasize the importance of contextual awareness and translator creativity in maintaining the integrity and impact of the original work.